2019
DOI: 10.17576/jsm-2019-4801-01
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying and the Enzymatic Activity in the Stomach of Amphiprion ocellaris Fed on Artificial Diet

Abstract: This study aims to elucidate the gastric emptying process of clownfish fed on artificial diet using two gastric evacuation models and to determine the pepsin activity in the digestion process in relation to feeding time. Regression analysis was used to evaluate the adequacy of 2 models; Anderson's [S t in describing the gastric emptying rate. Grove's model provided a better fit with higher r 2 value, with the calculated parameters of maximum meal size at time 0 (S 0 ) = 0.195 g and gastric emptying rate (K) =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Gut passage time is affected by many factors, such as the feeding regime (García-Ortega et al, 2010), feed quality (Nguyen et al, 2018), and temperature (Das et al, 2018;Volkoff and Rønnestad, 2020). Previous studies in A. ocellaris (Khoo et al, 2019) showed that 72-h fasting fish kept at 27 • C emptied the stomach after 36 h, and the gastric emptying rate depended on meal size. In the present study, the gut transit was faster at higher temperatures.…”
Section: Tablementioning
confidence: 99%
“…Gut passage time is affected by many factors, such as the feeding regime (García-Ortega et al, 2010), feed quality (Nguyen et al, 2018), and temperature (Das et al, 2018;Volkoff and Rønnestad, 2020). Previous studies in A. ocellaris (Khoo et al, 2019) showed that 72-h fasting fish kept at 27 • C emptied the stomach after 36 h, and the gastric emptying rate depended on meal size. In the present study, the gut transit was faster at higher temperatures.…”
Section: Tablementioning
confidence: 99%